Perkembangan Pendidikan Islam pada Masa Kesultanan di Nusantara - Destri Azahra; Fanny Oktavia Aggraeni; Mohammad Faiq Akmal (INDO PUBLISHING, 2026)
The development of Islamic education during the sultanate period in the Nusantara played an important role in shaping the education system and the character of society. However, today, understanding of the history and system of this education is still limited, especially among the younger generation. This study aims to identify and explain the development, system, and role of Islamic education during the sultanate period in the Nusantara. The research method used is qualitative with a library research approach, by examining various sources such as books and relevant journals. The results show that Islamic education during the sultanate period developed through institutions such as mosques, surau, dayah, and pesantren, which functioned as centers for religious learning as well as character building. In addition, the role of scholars (ulama) and the support of rulers greatly influenced the development of education at that time. The findings of this study also indicate that the Islamic education system during the sultanate period has values that are still relevant and can be applied in modern education today.